2022
DOI: 10.3389/fpsyg.2022.945294
|View full text |Cite
|
Sign up to set email alerts
|

The Working Alliance Inventory's Measurement Properties: A Systematic Review

Abstract: Measurement properties of the Working Alliance Inventory (WAI) and its various translations and adaptations for specific target groups have been investigated for over 30 years. No systematic review analyzing studies on measurement properties of the WAI has been conducted to date. COnsensus-based Standards for the selection of health Measurements INstruments (COSMIN) were developed for conducting high-quality systematic reviews on measurement properties in a transparent and standardized way. Aim of this study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 107 publications
0
6
0
1
Order By: Relevance
“…Although the WAI-SP is widely used, research that has evaluated the psychometric properties of the instrument has revealed inconsistencies in its internal structure; which were mostly examined by means of exploratory and confirmatory factor analysis, yielding divergent results of 1, 2, and 3 factors, including proposals for bifactor models. 6 , 20 , 37 For example, the original WAI-SP study found that the bifactor model, which includes one general factor and three specific factors, had a better fit in both the patient and therapist versions, 36 This measurement model has also been replicated in a study conducted in Norway. 38 In addition, the three-factor correlated structure of the WAI-SP has been validated in different countries.…”
Section: Introductionmentioning
confidence: 89%
“…Although the WAI-SP is widely used, research that has evaluated the psychometric properties of the instrument has revealed inconsistencies in its internal structure; which were mostly examined by means of exploratory and confirmatory factor analysis, yielding divergent results of 1, 2, and 3 factors, including proposals for bifactor models. 6 , 20 , 37 For example, the original WAI-SP study found that the bifactor model, which includes one general factor and three specific factors, had a better fit in both the patient and therapist versions, 36 This measurement model has also been replicated in a study conducted in Norway. 38 In addition, the three-factor correlated structure of the WAI-SP has been validated in different countries.…”
Section: Introductionmentioning
confidence: 89%
“…The WAI‐SF has been utilized for several years as a tool to assess the perceived strength of WA in psychotherapy and in various healthcare contexts. Its psychometric properties have been established in several studies (Busseri & Tyler, 2003; Del Re et al., 2012; Fenton et al., 2001; Flückiger et al., 2018; Horvath & Greenberg, 1989, Horvath & Symonds, 1991; Munder et al., 2010), although a recent systematic review (Paap et al., 2022), encompassing 66 studies published between 1989 and 2021, has shown inconsistent findings of reliability and validity of the WAI‐SF using rigorous criteria adopted by the consensus‐based Standards for the Selection of Health Measurement Instruments (COSMIN). However, these authors have recognized that COSMIN criteria may not be adequate for evaluating the measurement properties of instruments within the context of psychological research, and have advocated the development of new strategies to assess the psychometric properties of tools aimed at assessing conceptually complex domains, such as WA.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, since the WAI was originally developed to assess the working alliance between therapists and psychotherapy patients, research recommended that the measurement properties of the WAI should continue to be evaluated when applying to a diferent setting or diferent target population [25]. Hence, the psychometric properties of the WAI were re-evaluated for the target population of this study.…”
Section: Methodsmentioning
confidence: 99%